Quantification of strong and weak acidities in bio-oil via non-aqueous potentiometric titration - Wu, Liping; Hu, Xun; Mourant, D.; Wang, Y.; Kelly, Cyril; Garcia-Perez, M.; He, M.; Li, Chun-Zhu (Elsevier Ltd, 2013)
In this study a non-aqueous potentiometric titration method has been developed to quantify the carboxylic acids and phenolics in bio-oil. Quarternary ammonium hydroxide was used as the titrant and a mixture of tert-butanol and acetone was used as the solvent to differentiate the acidic components with distinct acidities. The heavy carboxylic acids, which cannot be identified with GC–MS, account for ca. 29–45% (mol basis) of all the carboxylic acids in the bio-oil from mallee wood. In addition, both the heavy and light phenolic components could be identified with the titration method developed, while GC–MS can only identify some light phenolic compounds (3% mol basis). The titration method was further applied to the determination of the concentrations of acidic components in the bio-oils from mallee wood, bark and leaves. The pyrolysis of mallee wood produced the highest yields of acidic components while that of leaves produce the lowest. The successful development of the titration method for quantification of these heavy carboxylic acids and phenolics provides useful information for the further upgrading of bio-oil.